Boro/carbothermal reduction co-synthesis of dual-phase high-entropy boride-carbide ceramics. Issue 6 (June 2023) - Feng, Lun; Fahrenholtz, William G.; Hilmas, Gregory E.; Curtarolo, Stefano
Abstract: Dense, dual-phase (Cr, Hf, Nb, Ta, Ti, Zr)B2 -(Cr, Hf, Nb, Ta, Ti, Zr)C ceramics were synthesized by boro/carbothermal reduction of oxides and densified by spark plasma sintering. The high-entropy carbide content was about 14.5 wt%. Grain growth was suppressed by the pinning effect of the two-phase ceramic, which resulted in average grain sizes of 2.7 ± 1.3 µm for the high-entropy boride phase and 1.6 ± 0.7 µm for the high-entropy carbide phase. Vickers hardness values increased from 25.2 ± 1.1 GPa for an indentation load of 9.81 N to 38.9 ± 2.5 GPa for an indentation load of 0.49 N due to the indentation size effect. Boro/carbothermal reduction is a facile process for the synthesis and densification of dual-phase high entropy boride-carbide ceramics with both different combinations of transition metals and different proportions of boride and carbide phases.